Early childhood development: child -to-child approach - Hashima-E-Nasreen; Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2020)
In Bangladesh, programs for children up to five years have been directed to ensure their survival, physical growth and good health. There is no nation wide structured program that addresses the cognitive, emotional, and social development of young children, resulting in lost opportunities to develop full potential of the child during the early years. Taking this into consideration, the Early Childhood Development (ECD) program has been initiated in the current country program cycle (2001-2005) of the Government and UNICEF. One of the strategies is to accomplish this through "Child-to-child approach", a time honoured system by which older children is taking care of their younger siblings. The objective of the child-to-child approach is to provide adolescents with the knowledge and skills to interact creatively and effectively with the young children, and to develop skills of critical-thinking and problem solving.